Lead compensator design for single-phase quasi Z-source inverter - Yong, S.; Law, K.; Ng, Wendy; Dahidah, M. (2018)
This paper presents a new control method for single-phase quasi-Z-source inverter (qZSI). At present, trial and error, as well as tuning of traditional proportional integral (PI) controller techniques, are utilized at the aforementioned topology to achieve system stability. Nevertheless, drawbacks of PI controlled based converter/inverter topologies are realized which include slow response speed and poor robust performance compared with the systems uncertainties and exogenous disturbances. In this work, lead compensator in control of the unipolar sinusoidal pulse width modulation (SPWM) qZSI is demonstrated to show its superiority against traditional PI control based on the derived qZSI's small signal model. The methods to obtain the controllers' parameters of the lead compensator is also documented in this paper. The effectiveness and the theoretical analysis of the proposed approach are verified through simulation studies for different loading conditions. The simulation demonstrates the correctness and effectiveness of the proposed control method in providing fast dynamic and transient response through frequency response analysis.